“Private banking” and competitive advantages of Russian medium-sized banks - S. S. Mikheyev; M. V. Sbruykina; V. A. Uspensky (Мир новой экономики)
Article is written by experts of the Russian banking sector and discusses the negative trends in the development of medium-sized banks in the Russian Federation. The main way to reverse the situation that the authors see potential in, is the use of the main competitive advantage of medium-sized banks - high flexibility. For medium-sized banks, it is desirable to choose the sphere of activity in which flexibility is a strategic necessity. One of the most attractive areas - Private Banking. It is proved that the active work with the main categories of wealthy clients (international language - HNWI and especially the less affluent ones - NWB) will contribute to a strengthening of the competitive position themselves medium-sized banks and stabilize the economic base of the entire existence of the middle class in Russia.